“UNDERSTANDING”: ESSENCE OF HERMENEUTIC - Anselmus Chartino Ade (LPPM Universitas Katolik Santo Thomas Medan, 2025)
Understanding refers to an ability to reach someone's personality. The focus point of hermeneutic philosophy is “the art of understanding”. Hermeneutic philosophers pay special attention to the interpretation and application of texts. Various things explain the difference further, such as: understanding with the heart and knowing with the head, understanding the whole and knowing part, understanding the depth and knowing the surface. People who have just arrived at knowing have not yet understood. The word hermeneutics or in English - hermeneutics can be derived from the Greek word hermeneuein which means “to translate” or “to act as an interpreter”. In the activity of translating a foreign language text into our own language, we must first understand and then try to articulate our understanding to others through our choice of words and series of translations. If we talk about hermeneutics in philosophy, we must take into account the distinctive contribution of the humanists in the Renaissance, because it was through them that the activity of interpretation was extended beyond the discipline of biblical studies and entered non-religious areas.